2019
DOI: 10.1016/j.ygeno.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of cell-free DNA as a screening marker for parasite infections in dog

Abstract: Parasitic infections are common in stray dogs and accurate knowledge of parasite communities in dogs would provide insight into the epidemiology of parasitic diseases. In this study, we used Illumina sequencing technology to evaluate cell-free DNA (cfDNA) as a marker for screening of parasitic infections in dogs. Plasma samples from 14 stray dogs captured in Bangladesh were used in the experiments. An average of 2.3 million reads was obtained for each sample. BLASTn analysis identified 150 reads with high simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…At this point, the DNA becomes "cell-free DNA" and is rapidly degraded into small fragments through the action of circulating enzymes known as "DNAses." As a result, most cfDNA fragments found in circulation are typically short, averaging 167 nucleotides in length in both humans and dogs (166,167). While both healthy cells and tumor cells contain DNA that becomes cfDNA in circulation, only tumor cells will harbor somatic genomic alterations in cancer-related genes.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, the DNA becomes "cell-free DNA" and is rapidly degraded into small fragments through the action of circulating enzymes known as "DNAses." As a result, most cfDNA fragments found in circulation are typically short, averaging 167 nucleotides in length in both humans and dogs (166,167). While both healthy cells and tumor cells contain DNA that becomes cfDNA in circulation, only tumor cells will harbor somatic genomic alterations in cancer-related genes.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Published research on canine cfDNA has covered a variety of clinical applications, including trauma, sepsis, thromboembolism, and neoplasia, and has focused primarily on determining the concentration of cfDNA in plasma as correlated to a particular clinical state or as a predictor for certain clinical outcomes (84, 148-151, 167, 169, 191-203). Studies that evaluated cfDNA concentrations in healthy canine subjects have reported median concentrations ranging from less than 1 ng/mL to greater than 500 ng/mL (148,149,167,169,(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)-significantly wider than the range documented in healthy humans (typically 0-20 ng/mL) (204). These wide-ranging findings suggest that additional research employing wellcontrolled, large-scale studies is required to better understand the fundamental characteristics of cfDNA in dogs; they also point to the need for standardized, reproducible methods for blood collection, extraction, and measurement of canine cfDNA.…”
Section: Cfdna Origins and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs with a cfDNA of higher than 1.118 value had a 98% probability of being dealt with due to the cfDNA integrity index. Circulating cfDNA are short fragmented DNA (22) that can be detectable in serum or plasma in order to be puri ed, quanti ed, and ultimately specially ampli ed via way of means of polymerase chain reaction (PCR) (23). On the other hand, way to an upward push in cell death leading to an extended quantity of DNA fragments diffusing into a move in which acute ailment tactics had notably better elevations in brief cfDNA concentrations than continual ones (24).…”
Section: Discussionmentioning
confidence: 99%
“…A value lower than the cutoff value (1.118) turned into taken into consideration awful prognosis, and smaller values have seemed like successful treatment. Interestingly, Akter et al (23) has already reported that cfDNA in blood will be an ability screening marker for guring out parasite variety in dogs.…”
Section: Discussionmentioning
confidence: 99%